Bauhaus at exhibitions in USSR. 1924–1932 - Efrussi, Tatiana A. (Actual Problems of Theory and History of Art, 2012)
In spite of the interest to the heritage of Bauhaus both in Russia and abroad, the problem тof participation of this school in the Soviet exhibitions has never been deeply researched. The reason was the lack of data and the bias of Bauhaus historiography. With the help of the sources discovered in Russian, German and Ukrainian archives the author tries to construct a chronology of these exhibitions, considered as steps of relations between Bauhaus and Soviet Union.